M-Au/TiO2 (M = Ag, Pd, and Pt) nanophotocatalyst for overall solar water splitting: role of interfaces - Melvin, Ambrose A.; Illath, Kavya; Das, Tanmay; Raja, Thirumalaiswamy; Bhattacharyya, Somnath; Gopinath, Chinnakonda S. (Nanoscale, 2015)
M-Au/TiO2 (M = Ag, Pd, Pt) composites were prepared through a facile one-pot photodeposition synthesis and evaluated for solar water splitting (SWS) with and without a sacrificial agent. The M-Au combination exhibits a dominant role in augmenting the H2 generation activity by forming a bi-metallic system. Degussa P25 was used as a TiO2 substrate to photodeposit Au followed by Au + M (M = Ag/Pd/Pt). The SWS activity of the M-Au/TiO2 was determined through photocatalytic H-2 production in the presence of methanol as a sacrificial agent under one sun conditions with an AM1.5 filter. The highest H-2 yield was observed for Pt-0.5-Au-1/TiO2 and was around 1.3 +/- 0.07 mmol h(-1) g(-1), with an apparent quantum yield (AQY) of 6.4%. Pt-0.5-Au-1/TiO2 also demonstrated the same activity for 25 cycles of five hours each for 125 h. Critically, the same Pt-0.5-Au-1/TiO2 catalyst was active in overall SWS (OSWS) without any sacrificial agent, with an AQY = 0.8%. The amount of Au and/or Pt was varied to obtain the optimum composition and it was found that the Pt0.5-Au1/TiO2 composition exhibits the best activity. Detailed characterization by physico-chemical, spectral and microscopy measurements was carried out to obtain an in-depth understanding of the origin of the photocatalytic activity of Pt-0.5-Au-1/TiO2. These in-depth studies show that gold interacts predominantly with oxygen vacancies present on titania surfaces, and Pt preferentially interacts with gold for an effective electron-hole pair separation at Pt-Au interfaces and electron storage in metal particles. The Pt in Pt-0.5-Au-1/TiO2 is electronically and catalytically different from the Pt in Pt/TiO2 and it is predicted that the former suppresses the oxygen reduction reaction.

Molybdenum carbide catalyst for the reduction of CO2 to CO: surface science aspects by NAPPES and catalysis studies - Reddy, Kasala Prabhakar; Dama, Srikanth; Mhamane, Nitin B.; Ghosalya, Manoj K.; Raja, Thirumalaiswamy; Satyanarayana, Chilukuri V.; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Carbon dioxide is a greenhouse gas, and needs to be converted into one of the useful feedstocks, such as carbon monoxide and methanol. We demonstrate the reduction of CO2 with H-2 as a reducing agent, via a reverse water gas shift (RWGS) reaction, by using a potential and low cost Mo2C catalyst. Mo2C was evaluated for CO2 hydrogenation at ambient pressure as a function of temperature, and CO2 : H-2 ratio at a gas hourly space velocity (GHSV) of 20 000 h(-1). It is demonstrated that the Mo2C catalyst with 1 : 3 ratio of CO2 : H-2 is highly active (58% CO2 conversion) and selective (62%) towards CO at 723 K at ambient pressure. Both properties (basicity and redox properties) and high catalytic activity observed with Mo2C around 700 K correlate well and indicate a strong synergy among them towards CO2 activation. X-ray diffraction and Raman analysis show that the Mo2C catalyst remains in the beta-Mo2C form before and after the reaction. The mechanistic aspects of the RWGS reaction were determined by near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) with in situ generated Mo2C from carburization of Mo-metal foil. NAPXPS measurements were carried out at near ambient pressure (0.1 mbar) and various temperatures. Throughout the reaction, no significant changes in the Mo2+ oxidation state (of Mo2C) were observed indicating that the catalyst is highly stable; C and O 1s spectral results indicate the oxycarbide species as an active intermediate for RWGS. A good correlation is observed between catalytic activity from atmospheric pressure reactors and the electronic structure details derived from NAPXPS results, which establishes the structure-activity correlation.

MnXWO4 nanostructure-based catalysts for single-step oxidation of cyclohexane and methane to oxygenates - Prabu, Marimuthu; Manikandan, Marimuthu; Samal, Pragnya Paramita; Gurrala, Lakshmi Prasad; Mekala, Siva Prasad; Archana, Ramakrishnan; Nayak, Chandrani; Bhattacharyya, D.; Jha, S. N.; Krishnamurty, Sailaja; Raja, Thirumalaiswamy (ACS Applied Nano Materials, 2023)
Activation of the C-H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on MnxWO4 nanostructures within 6 h. The recyclability test confirmed the catalyst heterogeneity, which revealed no appreciable loss of catalytic activity even after three consecutive reactions. In situ DRIFT study reveals that CYH is oxidized to cyclohexanone and cyclohexanol (KA oil) and is further oxidized to AA via carboxylate intermediates. DFT studies disclosed that MnOx species are responsible for the C-H activation of CYH, and the Mn2+/Mn3+ redox centers play a vital role in the absorption of KA oil to form AA. Herein, we demonstrated the significant role of the ``MnOx'' species and that adequate Lewis and Bronsted acidic sites, redox centers of (Mn2+/Mn3+), and lattice oxygen are accountable for the CYH conversion toward the AA. Additionally, we have reported the oxidation of methane to methanol (146 mu mole per gram of catalyst) in the presence of water at 75 degrees C without over-oxidation products.
Keywords: Adipic Acid; C-H bond activation; Cyclohexane oxidation; methane activation; MnOx chain; Redox center